Hak Asasi Manusia Dalam Perspektif Hukum Tata Negara - Khoirunnisa, Asyifa (JURNAL RUANG HUKUM, 2024)
This study discusses human rights from the perspective of constitutional law. Human Rights (HAM) are fundamental rights inherent in every individual, and are guaranteed through various legal instruments, including in the constitutional law system. In Indonesia, human rights are comprehensively regulated in the 1945 Constitution of the Republic of Indonesia (UUD 1945), especially in Articles 28A to 28J. This regulation is also supported by various other laws, such as Law No. 39 of 1999 concerning Human Rights and Law No. 12 of 2005 concerning Ratification of the International Covenant on Civil and Political Rights. This study adopts a qualitative method with a normative approach, which is carried out through an analysis of applicable laws and regulations and a review of related literature. The results of the study indicate that although Indonesian constitutional law has accommodated the protection of human rights, there is still a need to make further efforts in law enforcement and the development of more progressive policies. This is important to ensure that citizens' rights can be respected and enforced fairly.